Potential of Bacterial species as biocontrol agents of Fusarium wilt disease - Annadurai. R,; Kamaraj. M, (The Bioscan, 2024)
In this work aimed to evaluate the efficiency of biological products based on Bacterial species in the control of Fusarium species under in vitro conditions. Six rhizospheric bacterial isolates obtained from various field of cotton crop were screened in vitro by dual plate assay for antagonistic activity against Fusarium wilt pathogens. Their ability to B4 was found to be the most potential antagonist with a mycelial inhibition percentage of against FO3 and FO1 mycelia followed by FO4 and FO2 respectively. For the secondary metabolites screening in liquid media, 6 antagonistic bacteria against Fusarium sp. were selected with broad spectrum of PGPR. The result of the ethyl acetate extracted product of the bacterial isolates namely B3 and B4, against the two pathogen F3 and F1 are as given the NIST and WILEY library based on their retention time, molecular weight, molecular formula and one chemical structure of the compounds are illustrated by GCMS analysis.